The Activity of Mixed Microalgae Polysaccharides from Indonesia as Anti-Malaria in Vitro - Mahendra Pujiyanto; Zhaza Afililla; Lilik Maslachah; Thomas Valentinus Widiyatno; Mochamad Donny Koerniawan; Eko Agus Suyono; Arief Budiman; Ulfah Juniarti Siregar; Lucia Tri Suwanti (Faculty of Fisheries and Marine Universitas Airlangga, 2022)
Highlight Research One of the content of microalgae that is beneficial for health is polysaccharides Polysaccharides of Indonesian microalgae can be promoted as anti-malarial Polysaccharides from Glagah, Spirulina and East Java microalgae inhibited the growth of plasmodium in vitro and had IC50 values of 3.18 µg/mL, 5.43µg/mL and 9.87 µg/mL, respectively Abstract Malaria is an infectious disease caused by protozoan parasites of the genus Plasmodium that categorized as deadliest diseases in the world. Artemisinin and its derivatives are still recommended drugs for malaria therapy, however, there have been indications that Plasmodium parasites are resistant to this drug. Therefore, a study on polysaccharides from microalgae may be a potential as bioactive compound for anti-malaria. The aim of this study was to determine the effectiveness of the mixed microalgae polysaccharides as anti-malarial in vitro. Polysaccharides were extracted from three microalgae Spirulina sp., mixed microalgae Glagah and mixed microalgae East Java using the alkaline extraction method. The anti-malarial activity test refers to the concentration of polysaccharides used in calculating the IC50 value by probit analysis. The concentration of polysaccharides of the three microalgae used were 0; 0.01; 0.01, 1, 10 and 100 µg/mL. The results showed that the IC50 values of polysaccharides of Glagah, Spirulina sp. and East Java microalgae were 3.18 µg/mL, 5.43µg/mL, and 9.87 µg/mL, respectively. In Conclusion, polysaccharides of Indonesian mixed microalgae can be promoted as anti-malarial.